2019
DOI: 10.7150/thno.37187
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care cervical cancer screening using deep learning-based microholography

Abstract: Most deaths (80%) from cervical cancer occur in regions lacking adequate screening infrastructures or ready access to them. In contrast, most developed countries now embrace human papillomavirus (HPV) analyses as standalone screening; this transition threatens to further widen the resource gap.Methods: We describe the development of a DNA-focused digital microholography platform for point-of-care HPV screening, with automated readouts driven by customized deep-learning algorithms. In the presence of high-risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The cell level phenotypes presented in WSI are affected by genotypes such as MSI at the molecular scale. With the continuous penetration of artificial intelligence (AI) into the field of medical imaging, researchers have sought solutions based on deep learning, a research area in AI, in a wide range of medical problems, such as prediction of gene mutations 14 and tumor-infiltrating lymphocytes 12 , and cancer screening 15 , 16 . Whereas traditional machine learning depends largely on human-selected features 17 , deep learning can learn features from the data, which makes it possible for researchers to discover untapped information 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The cell level phenotypes presented in WSI are affected by genotypes such as MSI at the molecular scale. With the continuous penetration of artificial intelligence (AI) into the field of medical imaging, researchers have sought solutions based on deep learning, a research area in AI, in a wide range of medical problems, such as prediction of gene mutations 14 and tumor-infiltrating lymphocytes 12 , and cancer screening 15 , 16 . Whereas traditional machine learning depends largely on human-selected features 17 , deep learning can learn features from the data, which makes it possible for researchers to discover untapped information 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…developed a DNA‐focused digital micro holography method for HPV screening, with automated methods using deep‐learning algorithms. The result of this paper shows the excellent sensitivity and specificity (100% concordance) in detecting HPV 16 and 18 DNA from cell lines 79 …”
Section: Use Of DL Techniques For the Cancers Diagnosismentioning
confidence: 67%
“…Pathania et al developed a DNA-focused digital micro holography method for HPV screening, with automated methods using deep-learning algorithms. The result of this paper shows the excellent sensitivity and specificity (100% concordance) in detecting HPV 16 and 18 DNA from cell lines 79. Sompawong et al presented the method for detecting cervical cancer employing Pap smear histology slides using the Mask Regional Convolution Neural Network (Mask R-CNN).…”
mentioning
confidence: 82%
“…The system highlighted the patients who are at high risk of developing CIN2/3+, demonstrated that some infections involving multiple HPV types carry additional risks, and identified the most important gene combinations (29). Pathania proposed the HPV AI surveillance, which uses a deep learning (DL) algorithm combined with digital micro-holography, and reported excellent sensitivity and specificity (100% coincidence) in detecting HPV 16 DNA and HPV 18 DNA in cell lines (30). However, more studies are underway.…”
Section: Hpv Typing and Detectionmentioning
confidence: 99%